2018
DOI: 10.1088/2399-1984/aad009
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Pr3+ luminescence in hafnium silicate films: combined atom probe tomography and TEM investigations

Abstract: Structural, chemical, and luminescence properties of Pr 3+-doped HfSiO x layers fabricated by radiofrequency magnetron sputtering were examined as a function of annealing temperature. Phase separation between SiO 2 and HfO 2 as well as the location of Pr 3+ dopants were investigated using atom probe tomography and transmission electron microscopy while optical properties of Pr 3+ ions were studied using photoluminescence measurements. As a result, (i) we evidenced the location of the Pr 3+ dopants in the HfO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…It is worth to note that the HfO 2 -based compounds were not well addressed early as a matrix for the rare-earth ions. Few groups only reported on the light emission obtained from Eu 3+ -doped HfO 2 nanotubes [7], Er 3+ -doped sol-gel SiO 2 -HfO 2 waveguides [8,9], and Nd 3+ , Er 3+ or Pr 3+ doped HfO 2 films [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth to note that the HfO 2 -based compounds were not well addressed early as a matrix for the rare-earth ions. Few groups only reported on the light emission obtained from Eu 3+ -doped HfO 2 nanotubes [7], Er 3+ -doped sol-gel SiO 2 -HfO 2 waveguides [8,9], and Nd 3+ , Er 3+ or Pr 3+ doped HfO 2 films [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The previous study of Si-rich HfO 2 films co-doped with rare-earth ions [10,11] showed that the bright photoluminescence (PL) in visible and infrared spectral ranges, related to the rare-earth ions, can be obtained from the films annealed either at 900-950 °C [10] or at 950-1050 °C [11]. The reasons of this phenomenon were unclear and required additional study.…”
Section: Introductionmentioning
confidence: 99%
“…The similar intensities of the 880nm Nd 3+ PL band related to the 4 F 3/2 → 4 I J (J = 9/2) radiative transition detected at the both excitations (resonant and non-resonant) give the evidence that the rare-earth ions are excited via energy transfer from the Si nanoclusters or host defects as well. Recently we have demonstrated such effect for the Er-doped and Pr-doped HfSiO films [8,9].…”
Section: Light-emitting Propertiesmentioning
confidence: 91%
“…However, in spite of mentioned advantages, the HfO 2based compounds up to now are not often addressed as a host for the rare-earth ions. Just a few groups reported on the light emission obtained from Eu 3+ -doped HfO 2 -based nanotubes [4], Er 3+ -doped sol-gel SiO 2 -HfO 2 waveguides [5][6][7], as well as Er 3+ or Pr 3+ doped HfO 2 -based thin films [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Some papers were related to the emission study in the HfO 2 films doped with the rare-earth elements, such as Nd, Er, Pr, etc. 7,[10][11][12][13][14] Among different rare-earth trivalent elements, the Er 3+ ion is one of the most popular due to its radiative transitions in the green ( 4 S 3/2 → 4 I 15/2 ) and infrared ( 4 I 13/2 → 4 I 15/2 ) spectral ranges being extensively used as an eye-safe source in the atmosphere, laser radar, and medical and surgical applications ( 4 I 11/2 → 4 I 13/2 ). 15,16 However, the number of papers related to the spectroscopic investigation of HfO 2 ;Er based materials is few.…”
Section: Introductionmentioning
confidence: 99%